KNOWLEDGE, ATTITUDE AND RELATED FACTORS OF PARENTS REGARDING INDOOR AIR POLLUTION AND HEALTH AT A SECONDARY SCHOOL IN HANOI CITY IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge, attitudes, and identify associated factors regarding indoor air pollution and its health effects among parents of students at Thanh Da Secondary School, Hanoi, in 2025.Subject and method: A cross-sectional study was conducted on 439 parents of students from grades 6 to 9. Data were collected via self-administered Google Forms with the support of the School Board and homeroom teachers. Associated factors were identified using logistic regression analysis with a 95% confidence interval.Results: The study recorded that 92.7% of parents had heard about indoor air pollution. The prevalence of good knowledge and positive attitudes was 51.2% and 50.3%, respectively. Factors associated with knowledge included occupation, religion, family structure, and the smoking status of the parents or their cohabitants. Positive attitudes were associated with gender, occupation, religion, cooking location, and family structure. Notably, parents with good knowledge were 34.5 times more likely to have a positive attitude compared to those with poor knowledge (95% CI: 20.26–58.60).Conclusion: Knowledge and attitudes regarding indoor air pollution and health among parents remain limited. Communication interventions should be strengthened, focusing on high-risk groups such as those with cooking areas near common living spaces or households with smokers.
Keywords: Indoor air pollution; Knowledge; Attitude; Parents; Students, Secondary School.